Pengaruh Dewan Direksi, Dewan Komisaris Dan Komite Audit Terhadap Kebijakan Hutang - Wulan Novianti; Eny Purwaningsih (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
This study aims to determine the effect of the board of directors, board of commissioners and audit committee on debt policy. As well as the size of the board of directors, board of commissioners and audit committee on debt policy obtained from financial statement data listed on the Indonesian stock exchange for the 2018-2020 period. This study uses a type of causal observation that functions to identify cause and effect between two or more variables. The sample in this study is the food and beverage sub-sector industry listed on the IDX during the period 2018-2020 using the purposive sampling method. There are 13 companies listed on the Indonesia Stock Exchange in accordance with the provisions or criteria of the research sample where the sample is 39 financial statements. The research method uses multiple regression analysis. The results of this study show that there is a simultaneous influence of the board of directors, board of commissioners, and audit committee on debt policy, the results also show that there is a partial influence of the board of directors that has no effect on debt policy, the board of commissioners and the committee audit have negative effect on debt policy.